العقيقة في الفقه الإسلامي: دراسة تحليلية مقارنة في المذاهب الفقهية الأربعة: ’Aqīqah in Islamic Jurisprudence: A Comparative Analytical Study Across the Four Schools of Jurisprudence - Ataullah Nazari; Ziauddin Haneef (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث العقيقة سنة إسلامية ثابتة عن النبي صلى الله عليه وسلم، إلا أنها صارت من السنن المهجورة في عصرنا الحاضر. يهدف البحث إلى إحياء هذه السنة وبيان أحكامها وفوائدها؛ متبعا في ذلك المنهج الوصفي التحليلي. فيبحث المقال عن مشروعية العقيقة، ووقتها، وشروطها، وأحكامها في المذاهب الأربعة، مع ترجيح القول بسنيتها مع سبب الرجحان. وكذلك تشمل الدراسة أهمية العقيقة في الشكر على نعمة المولود، وحمايته من الشيطان، والدعاء له بالهداية، والتكافل الاجتماعي. وخلصت الدراسة إلى وجوب إحياء هذه السنة، والتمسك بها، وضرورة استبدال العادات الجاهلية بأحكام الشرع فيما يتعلق بالمولود. ABSTRACT ’Aqiqah is an established Islamic tradition from Prophet Muhammad, peace be upon him, but it is rarely practiced today. The research aims to revive this tradition and explain its rulings and benefits, using a descriptive analytical methodology. The article examines the legitimacy of ’aqiqah, its timing, conditions, and rulings in the four schools of jurisprudence, weighing in favor of its recommended status with the reason for preference. The study demonstrates the importance of ’aqiqah in giving thanks for the blessing of the newborn, protecting him from Satan, supplicating for his guidance, and social solidarity. The study concludes with the necessity of reviving this tradition, adhering to it, and replacing ignorant customs with Islamic rulings regarding the newborn.